2008
DOI: 10.1080/09540120701661690
|View full text |Cite
|
Sign up to set email alerts
|

The greater involvement of people living with AIDS principle: theory versus practice in Ontario's HIV/AIDS community-based research sector

Abstract: Drawing on the Greater Involvement of People with HIV/AIDS (GIPA) principle, the HIV/AIDS movement began to "democratize" research in Canada in the mid-1990s. To date, there is little evidence about the success of the community-based research (CBR) movement in relation to the implementation of GIPA. We draw on findings from a larger study examining barriers and facilitating factors in relation to HIV-related CBR in Ontario, Canada. An online survey was completed by 39 senior managers in Ontario AIDS service or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…More recently, Solomon and colleagues (2011) implemented and evaluated a model linking PLWH with experienced HIV clinicians to mentor junior rehabilitation professionals new to HIV care (mentees). Having both a clinical mentor and a mentor living with HIV was perceived by mentors and mentees as a strength, and honored the Greater Involvement of People living with AIDS principles (Travers et al, 2008). Hence, we built on this work to include mentors living with HIV as a key component in the nursing mentorship intervention.…”
Section: Canadian Hiv Mentorship Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Solomon and colleagues (2011) implemented and evaluated a model linking PLWH with experienced HIV clinicians to mentor junior rehabilitation professionals new to HIV care (mentees). Having both a clinical mentor and a mentor living with HIV was perceived by mentors and mentees as a strength, and honored the Greater Involvement of People living with AIDS principles (Travers et al, 2008). Hence, we built on this work to include mentors living with HIV as a key component in the nursing mentorship intervention.…”
Section: Canadian Hiv Mentorship Modelsmentioning
confidence: 99%
“…Community-based research has the potential to contribute to capacity building and community development (Caine & Mill, 2016;Hacker et al, 2012;Israel et al, 2010) and to benefit both the research endeavor and the stakeholders involved (Flicker, Savan, Kolenda, Mildenberger, 2007). Our inclusion of PLWH as co-investigators and advisors to this research, as well as PLWH mentor participants, ensured that the research was grounded in Greater Involvement of People living with AIDS principles (Travers et al, 2008). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GIPA/MIPA has been defined and understood in a variety of ways within the literature (Stephens, 2004;Travers, et al, 2008), however the core idea is the commitment to ensuring that the voices of PHAs are heard (White, 2001) and that human rights are respected (Ontario AIDS Network, 2011). GIPA/MIPA is often considered a model of best practice in local, national, and international organizations that respond to the HIV/AIDS epidemic (Stephens, 2004;UNAIDS 1999UNAIDS , 2004).…”
Section: Gipa/mipa Principlesmentioning
confidence: 99%
“…They found that lack of resources, inadequate procedures for providing feedback, insufficient clarity about the purpose of consultation, unsuitable structures for encouraging meaningful engagement, and concern over the group representativeness of those involved, were all significant in interfering with meaningful involvement. Travers et al (2008) surveyed and interviewed senior managers from ASOs in Ontario about barriers and facilitators to PHAs being involved in Community-Based Research (CBR). Findings suggested that HIV related stigma, health challenges, lack of capacity, distrust, other priorities, lived experience not being valued, limited mentoring opportunities, and insufficient financial compensation all contributed to low PHA involvement in the research.…”
Section: Barriers To Meaningful Involvement With Asosmentioning
confidence: 99%